A two-step mass-conservation approach to infer ice thickness maps: Performance for different glacier types on Svalbard - Fürst, Johannes J.; Seehaus, Thorsten; Sass, Björn; Aas, Kjetil; Benham, Toby J.; Dowdeswell, Julian A.; Fettweis, Julian; Gillet-Chaulet, Fabien; Moholdt, Geir; Navarro Valero, Francisco José; Nuth, Christopher; Petterson, Rickard; et al. (E.T.S.I. Telecomunicación (UPM), 2017)
Satellite remote sensing based on optical or radar instruments has enable us to measure glacier-wide surface velocities as well as changes both in glacier extent and in surface elevation with good coverage worldwide.